Sleep problems in cancer patients: Prevalence and association with distress and pain - Sharma, N; Hansen, C; OConnor, M; Thekkumpurath, P; Walker, J; Kleiboer, A; Murray, G; Espie, C; Storey, D; Sharpe, M (2012)
Background Although it is increasingly recognized that cancer patients often have sleep problems, we lack data on their prevalence and associations in representative clinical populations. We aimed to determine (i) the prevalence of sleep problems amongst outpatients of a cancer centre and (ii) the association with medical variables, emotional distress and pain. Methods Secondary analysis of self-report and medical data on 2862 cancer centre outpatients. Sleep problems were identified using the sleep item from the Patient Health Questionnaire-9: 'Over the last two weeks, how often have you been bothered by trouble falling or staying asleep or sleeping too much?' scored on a four-point frequency scale. Emotional distress was measured using the Hospital Anxiety and Depression Scale and pain using the subscale of the European Organisation for Research and Treatment of Cancer Quality of Life Core 30 questionnaire. Medical data were obtained from the cancer centre clinical database. Results Sleep problems (bothered more than half the days during the previous 2 weeks) were reported by 30.2% (865/2862, 95% CI = 28.5 to 31.9) of the patients. They were common in both patients with active cancer (34.5%) and in cancer survivors (28.0%). There was only a modest association with cancer site and treatment status, but there was a strong association with pain (odds ratio = 2.7, 95% CI = 2.2 to 3.4) and emotional distress (odds ratio = 4.5, 95% CI = 3.7 to 5.6). Conclusions Sleep problems are common in cancer outpatients and are strongly associated with pain and emotional distress. A combined approach to the management of sleep, pain and emotional distress is indicated. Copyright © 2011 John Wiley and Sons, Ltd.